2007
DOI: 10.1126/science.1138562
|View full text |Cite
|
Sign up to set email alerts
|

The Variable Rotation Period of the Inner Region of Saturn's Plasma Disk

Abstract: We show that the plasma and magnetic fields in the inner region of Saturn's plasma disk rotate in synchronism with the time-variable modulation period of Saturn's kilometric radio emission. This relation suggests that the radio modulation has its origins in the inner region of the plasma disk, most likely from a centrifugally driven convective instability and an associated plasma outflow that slowly slips in phase relative to Saturn's internal rotation. The slippage rate is determined by the electrodynamic cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
323
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 228 publications
(362 citation statements)
references
References 24 publications
33
323
4
Order By: Relevance
“…Various models have been suggested to explain the properties of the Kronian magnetosphere (Espinosa et al, 2003;Southwood and Kivelson, 2007;Goldreich and Farmer, 2007;Gurnett et al, 2007;Southwood and Kivelson, 2009;Khurana et al, 2009;Carbary and Mitchell, 2013). Recently Jia and Kivelson (2012) proposed a numerical model, which agrees well with most of the experimental results currently known.…”
Section: Introductionsupporting
confidence: 72%
“…Various models have been suggested to explain the properties of the Kronian magnetosphere (Espinosa et al, 2003;Southwood and Kivelson, 2007;Goldreich and Farmer, 2007;Gurnett et al, 2007;Southwood and Kivelson, 2009;Khurana et al, 2009;Carbary and Mitchell, 2013). Recently Jia and Kivelson (2012) proposed a numerical model, which agrees well with most of the experimental results currently known.…”
Section: Introductionsupporting
confidence: 72%
“…Despite this, however, oscillations with a period near thẽ 11 h planetary period are observed throughout Saturn's magnetosphere. Such modulations are observed in the magnetic field, Saturnian kilometric radiation (SKR), plasma parameters, energetic particle fluxes, and associated neutral atom emissions, as well as auroral ultraviolet, infrared, and radio emissions [e.g., Warwick et al, 1981Warwick et al, , 1982Desch and Kaiser, 1981;Gurnett et al, 1981Gurnett et al, , 2007Gurnett et al, , 2010aSandel and Broadfoot, 1981;Sandel et al, 1982;Carbary and Krimigis, 1982;Espinosa and Dougherty, 2000;Krupp et al, 2005;Cowley et al, 2006;Kurth et al, 2007;Southwood and Kivelson, 2007;Carbary et al, 2007Carbary et al, , 2008aCarbary et al, , 2008bZarka et al, 2007;Andrews et al, 2008;Nichols et al, 2008Nichols et al, , 2010aNichols et al, , 2010bBurch et al, 2009;Provan et al, 2009aProvan et al, , 2009bClarke et al, 2006;Badman et al, 2012;Lamy et al, 2013]. Those oscillations were first observed in Voyager measurements of the SKR emissions, around the time of Saturn's northern hemisphere spring equinox [Kaiser et al, 1980].…”
Section: Introductionmentioning
confidence: 99%
“…[41] Gurnett et al [2007] have earlier suggested on the basis of asymmetries in electron density that there is a rotating circulation system in Saturn's magnetosphere which serves to carry ionized material injected in the inner magnetosphere by Enceladus out into interplanetary space. The sketch of the circulation given by Gurnett et al [2007, Figure 2b] shows a familiar two cell circulation pattern.…”
Section: Relation To Plasma Circulationmentioning
confidence: 99%